How to effectively utilize Microsoft Project 2010 with SharePoint 2010 - Sy, Dux Raymond (O'Reilly Media, 2011)
"Microsoft Project is a project management tool widely used by project managers today. Its ability to support project managers to define a schedule, assign resources to tasks and track project status has been instrumental in contributing to project success. However, it can be a challenge for a project manager to share project information and collaborate with the project team with Microsoft Project alone. Microsoft SharePoint 2010 can complement Microsoft Project 2010 and address this gap."--Resource description page.